Pengolahan Feses Sapi Dan Limbah Kol Dengan Metode Vermikompos Menggunakan Dekomposer Lumbricus Rubellus Ditinjau Dari Ph Suhu Dan Produksi Vermikompos - Handi Kusnadi; Novia Rahayu; Andri Kusmayadi (Fakultas Pertanian Universitas Majalengka, 2022)
The livestock sector has long been a source of livelihood for the people of Indonesia. In addition to having a positive impact, the increase in livestock business also has a negative impact, namely from the waste produced in the form of feces and urine. Vegetable waste is a waste material which is usually disposed of in open dumping without further management so that it will cause environmental disturbances and unpleasant odors. Recycling organic waste into something useful again can be done in various ways, among others, by making organic waste as earthworm feed which will later produce vermicompost fertilizer. This study used a completely randomized design (CRD) with 5 treatments and 4 replications, each treatment having a concentration of P0 = 100% cow feces + 0% cabbage waste, P1 = 75% cow feces + 25% cabbage waste, P2 = 50% cow feces 50 % Cabbage Waste, P3 = 25% Cow Feces + 75% Cabbage Waste, P4 = 0% Cow Feces + 100% Cabbage Waste. The results in this study are all treatments that produce temperature and pH are stated in accordance with SNI 19-7030-2004 the temperature is not more than 30 and the pH ranges from 6.80-7.49. While the production of vermicompost produces P3 as a treatment that produces the highest production, namely with a production of 1400 grams with a waste degradation of 40.0%.